Strategy and course curriculum for professional forestry education in India - Patil, V; Burley, J (Commenwealth Forestry Institute, University of Oxford, 1985)
Changes and reforms in professional forestry education in India are necessary in order to achieve the ambitious target of rehabilitation of 5 million hectares of land per year, while maintaining the management of current forest resources. The existing educational facilities are both inadequate and not commensurate with the changing needs. Hatch (1985) has estimated that over 900 new foresters must be recruited annually between now and 1990 to meet the requirements. The Government of India is now making efforts to bring about major changes in the field of professional forestry education. An important step in that direction is the development of undergraduate degree programmes in forestry in selected Agricultural Universities. In the long term it will probably be desirable that each State in India should develop a B.Sc. (Forestry) degree programme in an Agricultural University, extending it further to post-graduate degree programmes later. Sufficient care must be exercised in formulating the course curricula for such degree programmes. The course curricula should have a proper blend of subjects in forestry, agricultural and social sciences. An effort has been made to formulate a model for a four-year degree programme of Bachelor of Science (Forestry), and the outlines are given in Appendix I. All the B.Sc. (Forestry) graduates should undergo probationary internship of at least six months. At present all recruits to the Indian Forest Service (IFS) and to State Forest Services have to undergo an extended period of preservice training in forestry at the Forest Research Institute and Colleges, Dehra Dun, or at one of the State Forest Service Colleges. If the strategy and curriculum proposed here were accepted, there would not then be a need for pre-service training in forestry. However, the forestry graduates recruited for the IFS, may be given four months' administrative training.